The interface of value creation and service process: A categorization of the relevant perspectives and an integrative framework - Hannu Makkonen (jbm - Journal of Business Market Management, 2015)
The focal study considers the variety in recent perspectives on value and value creation in service as a stimulant to explicate and organize differences to build toward integrative understanding. The purpose of the study is to provide a categorization of the perspectives on value and value creation and to propose an integrative framework that illustrates how value, value creation, and the service process relate to each other. The study presents a conceptual analysis on the value creation and service literatures and employs the activity system model to structure relevant elements into an integrative research framework. The study contributes to the current understanding by defining and organizing the underpinning elements of value creation and service processes as well as explicating their mutual interface in the context of service systems. This aims to deliver conceptual clarity and a base for further research.
urn:nbn:de:0114-jbm-v8i3.1085
Keywords: 650; Interactive value formation; Value co-creation; Service co-production; Service-dominant logic; Customer-dominant logic; Activity system model